Anxiety & Coping Patterns Regarding Pubertal Changes among Pre-Adolescent Girls of Udupi Taluk, Karnataka - F., Sequeira D.; A., D'souza; E., Sanatombi Devi (Journal of Health and Allied Sciences NU, 2016)
Background: Puberty is a period in the developmental span when the individual changes from an asexual being to a sexual being.Objectives:The present study was aimed to assess the anxiety and coping pattern regarding pubertal changes among pre-adolescents girls in selected schools of Udupi Taluk, Karnataka.Materials and methods:The study included 540 pre-adolescent girls of age group (10-12years) from selected schools of Udupi Taluk by cluster random sampling technique. Data was collected using structured questionnaires.Results:The study showed that out of 231 pre-adolescents who attained menarche (55%) had moderate anxiety and 52.4% had adaptive coping pattern. Among 309 pre-adolescents who did not attain menarche, 62.1% had moderate level of anxiety and 53.4% had adaptive coping pattern regarding pubertal changes. It also showed that there was a negative correlation between anxiety and coping pattern of the pre-adolescent girls, r= -0.754.Conclusion: The study concluded that pre-adolescent girls have moderate level of anxiety and adaptive coping pattern regarding pubertal changes and it also showed that when anxiety increases coping pattern decreases. Majority of the respondents had moderate level of anxiety and adaptive coping pattern.
Keywords: Anxiety; puberty; coping pattern; pre-adolescents